MicroRNA6443‐mediated regulation of FERULATE 5‐HYDROXYLASE gene alters lignin composition and enhances saccharification in Populus tomentosa. Issue 2 (31st January 2020) - Fan, Di; Li, Chaofeng; Fan, Chunfen; Hu, Jian; Li, Jianqiu; Yao, Shu; Lu, Wanxiang; Yan, Yangyang; Luo, Keming
Summary: Ferulate 5‐hydroxylase (F5H) is a limiting enzyme involved in biosynthesizing sinapyl (S) monolignol in angiosperms. Genetic regulation of F5H can influence S monolignol synthesis and therefore improve saccharification efficiency and biofuel production. To date, little is known about whether F5H is post‐transcriptionally regulated by endogenous microRNAs (miRNAs) in woody plants. Here, we report that a microRNA, miR6443, specifically regulates S lignin biosynthesis during stem development in Populus tomentosa . In situ hybridization showed that miR6443 is preferentially expressed in vascular tissues. We further identified that F5H2 is the direct target of miR6443. Overexpression of miR6443 decreased the transcript level of F5H2 in transgenic plants, resulting in a significant reduction in S lignin content. Conversely, reduced miR6443 expression by short tandem target mimics (STTM) elevated F5H2 transcripts, therefore increasing S lignin composition. Introduction of a miR6443‐resistant form of F5H2 into miR6443‐overexpression plants restored lignin ectopic composition, supporting that miR6443 specifically regulated S lignin biosynthesis by repressing F5H2 in P. tomentosa . Furthermore, saccharification assays revealed decreased hexose yields by 7.5–24.5% in miR6443‐overexpression plants compared with the wild‐type control, and increased hexoses yields by 13.2–14.6% in STTM6443 ‐overexpression plants. Collectively, we demonstrate that miR6443 modulates S lignin biosynthesis by specially regulating F5H2 in P. tomentosa .